MEMAHAMI ORGANISASI DI LINGKUNGAN PESANTREN - Aziz, Abdullah Aminuddin (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This article intends to study the organization inboarding schools or pesantren. It is a form of institutionalizedIslamic education in Indonesia. The word cottage (rooms,huts, small houses) used in Indonesian with emphasis on thesimplicity of building. Conditions boarding school inIndonesia that using dormitories and boarding system,making boarding school populated by a wide variety oforigins and character of students. Foundation as anorganization that collects collective leadership and control ofthe existing leadership, has become an alternative toboarding institutions remain viable and survive (survive).However, there are many weaknesses in addition to theadvantages of course.Keywords: Pesantren, organization